111. Dose optimization in mammographic screening: results from ten years invigilation. (December 2018) - Busoni, S.; Taddeucci, A.; Gori, C.; Ambrogetti, D.; Mazzalupo, V.; Carnesciali, E.; Falini, P.; Mantellini, P.; Fedeli, L.
Abstract : Purpose: Mammographic screening represents one of the most significant medical expose to radiation for women. The method proposed from European Reference Organisation for Quality Assured Breast Screening and Diagnostic Services (EUREF) evaluate average glandular dose (AGD) considering the breast glandularity (BG) a function of breast thickness (BT). VOLPARA software (Volpara Solutions Limited) compute BG from acquired images using a multi-parametric algorithm. The purpose of this study is to evaluate the difference between AGD computed in both method and to assess the applicability of automatic tools for patient dose optimisation and mammographic unit QCs. Methods: Mammographic screening exams from last 10 years performed in our institution have been considered. More than 350'000 exams overall (total 1.5 M of expositions), from seven mammographic units (of three different vendors), were included in this study. Exams have been performed using automatic exposure control settings. Data was extracted from DICOM images and processed using VOLPARA software (Volpara Solutions Limited) and analysed with a custom Matlab software. For each exposition difference between Diff = AGD EUREF - AGD VOLPARA was determinated. Exposure data are retrieved to identify patient dose optimisation strategies and to track device performances. Results: Average Diff is 0.07 ± 0.13 mGy (min/max −1.7/+1.8 mGy), mean breast thickness is 55 mm (SD 13 mm min/max 10/117 mm). In figure is reported percent distribution of Diff as function of BT. Large part of exams shows Diff > 0 (71% of total), the remains have Diff < 0. Breast thickness distribution of two considered classes are: (mean ± sd) 60 ± 10 mm, 53 ± 14 mm respectively for Diff < 0 and Diff > 0. These results are generally reproducible among seven mammographic units considered. Conclusions: Presented results indicate EUREF approach overestimate AGD, the proposed method allow to assess personal dosimetry and could be implemented in order to monitor in live time AGD difference from EUREF evaluation. Use of automatic dose software allow to monitor possibly variation in exposition parameters.